2004
DOI: 10.1124/jpet.103.059394
|View full text |Cite
|
Sign up to set email alerts
|

Salvinorin A, an Active Component of the Hallucinogenic SageSalvia divinorumIs a Highly Efficacious κ-Opioid Receptor Agonist: Structural and Functional Considerations

Abstract: The diterpene salvinorin A from Salvia divinorum has recently been reported to be a high-affinity and selective -opioid receptor agonist (Roth et al., 2002). Salvinorin A and selected derivatives were found to be potent and efficacious agonists in several measures of agonist activity using cloned human -opioid receptors expressed in human embryonic kidney-293 cells. Thus, salvinorin A, salvinorinyl-2-propionate, and salvinorinyl-2-heptanoate were found to be either full (salvinorin A) or partial (2-propionate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
234
4
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(259 citation statements)
references
References 24 publications
17
234
4
4
Order By: Relevance
“…After an overnight serum depriva-tion, intracellular calcium flux assays were performed using a Molecular Devices Calcium Plus Assay kit and a FLEX Station II fluorescence plate reader (Molecular Devices). 46,47 with a few modifications. Briefly, cells were washed once with 100 ml serum-free, indicator-free DMEM.…”
Section: Mutagenesismentioning
confidence: 99%
“…After an overnight serum depriva-tion, intracellular calcium flux assays were performed using a Molecular Devices Calcium Plus Assay kit and a FLEX Station II fluorescence plate reader (Molecular Devices). 46,47 with a few modifications. Briefly, cells were washed once with 100 ml serum-free, indicator-free DMEM.…”
Section: Mutagenesismentioning
confidence: 99%
“…A planta Salvia divinorum (SDI), da família Lamiaceae, tem sido usada por séculos pela cultura mazateca (Wolowich et al, 2006) e vem ganhando popularidade como droga recreacional nos últimos anos (Chavkin et al, 2004;Grundmann et al, 2007). É uma erva perene, natural da serra mazateca de Oxaca, no México (Vortherms & Roth, 2006;Valdes, 1994).…”
Section: Revisãounclassified
“…O diterpeno SA, agonista kappa opióide de alta afinidade (Chavkin et al, 2004;Roth et al, 2002), tem potencial psicotrópico similar ao da mescalina (Giroud et al, 2000), porém com diferentes efeitos (Braida et al, 2007). Tem baixa biodisponibilidade oral, o que motivou a pesquisa de análogos como a N-metilacetamida (Béguin et al, 2007).…”
Section: Revisãounclassified
See 1 more Smart Citation
“…[2,4] Extensive receptor assays have indicated that salvinorin A acts selectively as a potent κ-opioid receptor (KOR) agonist [5,6] exhibiting similar efficacy to known KOR agonists U69,593 and TRK-820. [7] The biological properties of salvinorin A are unique, considering it is a non-nitrogenous opioid agonist and displays hallucinogenic effects similar to LSD 3, mescaline 4, and DMT 5 ( Fig. 1) while lacking structural similarity to these classical alkaloids.…”
Section: Introductionmentioning
confidence: 99%